Extra-articular Distal Humerus Bridging Plate: a Minimally Invasive Technique - Rezende, Luis Guilherme Rosifini Alves; Shimaoka, Filipe Jun; Mandarano-Filho, Luiz Garcia; Mazzer, Nilton (ARCHIVES OF HEALTH INVESTIGATION, 2022)
Extra-articular fractures of the distal humerus are challenging due to their peculiar location and anatomy. It challenges the surgeon to choose the best osteosynthesis method and approach. We present a minimally invasive technique by bridging the LCP Extra-articular distal humerus plate (DePuy-Synthes). The indication for this method was fractures classified as AO/OTA type 13A2 and 13A3. Concerns about the radial nerve pathway to avoid its injury are crucial to perform this method. Possible complications are shortening, rotational displacement, nerve injury and wrong plate and screw positioning.